Pengembangan LKPD Berbasis PJBL untuk Kemampuan Literasi Numerasi pada Materi Statistika - Pratama, Chintia Putri; Riyawati, Selvi; Etmy, Desventri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to produce Project Based Learning (PjBL) based Student Worksheets (LKPD) on Statistics material to support valid and practical numeracy literacy skills of eighth grade junior high school students. This research is a development research (Research and Development) using the 4D model (Define, Design, Develop, and Disseminate), but the research was only carried out up to the Develop stage. The research subjects consisted of two validators and 29 eighth grade students of SMP Negeri 10 Kota Bengkulu. The instruments used were validation sheets and practicality questionnaires. The validation results showed that the PjBL-based LKPD obtained an average percentage of 93.83% with a very valid category. The results of limited trials showed that the developed LKPD received a positive response from students so that it was included in the very practical category. PjBL-based LKPD on Statistics material facilitates students in data collection, data processing, data presentation, and data interpretation activities through contextual project activities. In conclusion, LKPD based on Project Based Learning on Statistics material is suitable for use as an alternative teaching material to support students' numeracy literacy skills. Keywords: Student Worksheet, Project Based Learning, Numeracy Literacy, Statistics, 4D Development Model.